Exploring New Students Perceptions in English Education Program at Universitas Kuningan on Pop Songs as a Motivation Tool in Learning English - Dera, Cicilia (Proceedings Series on Social Sciences & Humanities, 2025)
In recent years, pop songs have become increasingly popular as a tool to motivate students in learning English, particularly among younger learners. This study explores how new students in the English Education Program at Universitas Kuningan perceive the use of pop songs in supporting their motivation and language development. Specifically, the research investigates how pop songs influence students’ enthusiasm, what language skills they believe are improved through music, and which types of songs are most effective in boosting motivation. Using a qualitative method, data were gathered through open-ended questionnaires completed by ten first-year students. Their responses were then analyzed thematically to identify common patterns and insights. The results show that most students responded positively, saying that pop songs made learning English more enjoyable, less boring, and emotionally engaging. Many reported noticeable progress in vocabulary, pronunciation, and listening skills, along with greater confidence in speaking English. Songs with slower tempos, clear pronunciation, and relatable themes particularly those by popular artists such as Taylor Swift, Coldplay, and BTS, were seen as especially motivating. Although some students mentioned challenges like slang or fast-paced lyrics, they generally viewed these as opportunities to improve rather than barriers. Overall, the study concludes that pop songs meet students’ psychological needs for autonomy, competence, and relatedness, aligning with the principles of Self-Determination Theory. As such, pop songs can be considered an effective and informal strategy to enhance both motivation and language skills in English learning.